2021
DOI: 10.1016/j.clnu.2020.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypophosphatemia in the ICU – Results of an international one-day point prevalence survey

Abstract: Background & aims: Hypophosphatemia (HypoP) is associated with organ dysfunction and mortality. Despite its potential severe consequences, HypoP remains poorly characterized in terms of real prevalence and timing of onset. The primary objective was to determine the prevalence of HypoP defined as blood phosphate <0.8 and < 0.65 mmol/l on one particular day at international level. Methods: One-day point prevalence survey conducted by the Section of Metabolism, Endocrinology and Nutrition (MEN) of the European So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Previous studies have discovered that the incidence of hypophosphatemia ranged from 15.4% to 71.6% in a variety of patients, including critically ill children and adults, patients with acute kidney injury and those with massive burns. [14][15][16][17][18][19][20][21] The correlation between increased mortality and occurrence of hypophosphatemia was also confirmed in these studies. We designed this study to explore the incidence of hypophosphatemia at admission in COVID-19 patients and to verify whether hypophosphatemia was associated with mortality in COVID-19 patients.…”
Section: Introductionsupporting
confidence: 64%
“…Previous studies have discovered that the incidence of hypophosphatemia ranged from 15.4% to 71.6% in a variety of patients, including critically ill children and adults, patients with acute kidney injury and those with massive burns. [14][15][16][17][18][19][20][21] The correlation between increased mortality and occurrence of hypophosphatemia was also confirmed in these studies. We designed this study to explore the incidence of hypophosphatemia at admission in COVID-19 patients and to verify whether hypophosphatemia was associated with mortality in COVID-19 patients.…”
Section: Introductionsupporting
confidence: 64%
“…Due to significant variations in RFS definitions, its exact incidence remains unknown. However, when RFS is defined by hypophosphatemia (hypoP) with a cut-off level of 0.65 mmol/L, the incidence ranges from 34 to 40%, with 4–10% presenting severe hypophosphatemia (phosphate < 0.32 mmol/L) or a drop after the start of glucose infusion or nutrition therapy [ 111 113 ]. Most recent studies in ICU patients using hypoP as the primary criterion to define RFS did not identify clinical predictors of RFS on ICU admission [ 41 , 110 , 114 ].…”
Section: Question 9: How To Screen and Manage Patients For Refeeding Syndrome?mentioning
confidence: 99%
“…In ICU patients, phosphate level might change faster than in non-ICU population, with consequences being potentially more severe. A recent point-prevalence survey in ICU patients defined severe hypophosphatemia as Pi<0.65 mmol/l [14]. Hereafter, the values will be reported according to the authors' definitions in respective studies.…”
Section: General Considerationsmentioning
confidence: 99%
“…Symptoms of hypophosphatemia are non-specific, yet potentially lifethreatening, and include muscle weakness, impaired myocardial contractility and ventricular arrhythmias, respiratory failure, rhabdomyolysis, ileus, immune dysfunction, encephalopathy, and hypercalciuria [1,5]. Despite the presumed importance of maintaining normal phosphate concentration in both health and disease states, and the common presence of risk factors of hypophosphatemia, several recent surveys have indicated that routine phosphate monitoring is not widespread in patients admitted to intensive care units (ICU) and that hypophosphatemia is often not corrected [6,7].…”
Section: Introductionmentioning
confidence: 99%